2019
DOI: 10.9734/ajmah/2019/v16i130134
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Pattern of Nitrofurantoin of Uropathogens in Different Age Groups at Dr. Lal Path Labs, National Reference Laboratory, Rohini, Delhi

Abstract: Aims and Objectives: This study was undertaken to highlight the resistance pattern of Nitrofurantoin among 5162 UTIs causing isolates at Microbiology Department of Dr. Lal Path Labs between April to June 2019. Materials and Methods: This retrospective study was performed in Department of Microbiology at Dr. Lal Path Labs, Delhi during period April to June 2019. Standard loopful midstream urine samples collected in a sterile container were inoculated on UTI Chromagar and incubated overnight at 37ºC and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They found nitrofurantoin to be effective against 69.9% of E. coli isolates. 15 Sood et al studied antibiotic resistance in various uropthogens and found E.coli to account for 61.84% isolates. They found nitrofurantoin resistance in only 5-6% E.coli isolates.…”
Section: Resultsmentioning
confidence: 99%
“…They found nitrofurantoin to be effective against 69.9% of E. coli isolates. 15 Sood et al studied antibiotic resistance in various uropthogens and found E.coli to account for 61.84% isolates. They found nitrofurantoin resistance in only 5-6% E.coli isolates.…”
Section: Resultsmentioning
confidence: 99%